The Effect of Financial Literacy, Locus of Control and Life Style on the Financial Behavior of Peer to Peer Lending Paylater User In Surabaya City - Berlianti, Selvina Novantia; Suwaidi, Rahman Amrullah (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Paylater is the latest payment system issued by e-commerce that we can shop for anything and paylater (buy now pay later). However, this convenience makes people more consumptive. This study aimed to determine how financial literacy, locus of control, and lifestyle factors influence the financial behavior of Paylater users in Surabaya. The sample will consist of 100 respondents who will be chosen using the Cochran method and a purposive sampling technique. The data analysis method applied is Partial Least Square (PLS). The results of this study indicate that financial literacy, locus of control, and lifestyle all play a role in influencing financial behavior.